Wolf spider burrows from a modern saline sandflat in central Argentina: Morphology, taphonomy and clues for recognition of fossil examples - Mendoza Belmontes, Fatima del Rosario (2018)
Pavocosa sp. (Lycosidae) burrows found in an open sparsely vegetated area on the edge of the Gran Salitral saline lake, in central Argentina, are described. Burrows were studied by capturing the occupant and casting them with dental plaster. The hosting sediments and vegetation were also characterized. Inhabited Pavocosa sp. burrows display distinctive features as open, cylindrical, nearly vertical, silk lined shafts about 120 mm long, subcircular entrances, a gradual downward widening, and a particularly distinctive surface ornamentation in the form of sets of two linear parallel marks at a high angle to the burrow axis. Instead, casts of vacated Pavocosa sp. burrows showed some disturbances caused either by the reoccupation by another organism or by predation of the dweller. Two morphologies are related to reoccupation of burrows: those with a structure in form of an ``umbrella'' and another with smaller excavations at the bottom of the burrow. Predation by small mammals produces funnel-shaped burrows. Both active and abandoned Pavocosa sp. burrow casts are compared with existing ichnogenera and inorganic sedimentary structures, highlighting its distinction. It is argued that key features like the presence of a neck, a downward widening and the described surface texture will allow recognition of wolf spider burrows in the fossil record. However, the putative spider burrows described in the literature either lack the necessary preservational quality or do not show ornamentation similar to the modern wolf spider burrows. Fossil wolf spiders are recorded since the Paleogene (possibly Late Cretaceous), therefore Cenozoic continental rocks can contain wolf spider burrows awaiting recognition. In addition, the particular distribution of Pavocosa sp. in saline lakes may imply that this type of burrow is linked to saline environments.